A perched, high-elevation wetland complex in the Atacama Desert (northern Chile) and its implications for past human settlement - Sitzia, Luca; Gayo, Eugenia M.; Sepulveda, Marcela; Gonzalez, Juan S.; Ibanez, Lucia; De Pol Holz, Ricardo Hernán; De Pol-Holz, Ricardo (My University, 2019)
A previously undocumented type of wetland is described from the Atacama Desert in northern Chile (3000 m above sea level), sustained exclusively by direct precipitation and perched above the regional water table. Geomorphological mapping, pedostratigraphy, geochemistry, and analysis of contemporary vegetation is used to understand wetland formation and dynamics during historical and present time periods. The paleowetland deposits overlie a Miocene tuff that acts as an impermeable barrier to water transfer and creates conditions for local shallow ground water. These deposits include several paleosols that were formed during periods when precipitation increased regionally at 7755-7300, 1270, 545, and 400-300 cal yr BP. The similarity in timing with other palaeohydrological records for the Atacama implies that paleosols from this wetland are proxies for reconstructing past changes in local and regional hydrological cycle. Archaeological investigations have revealed the presence of two small farms from the Late Intermediate period, i.e., during the earliest wetter phase represented by the paleosols. Both farms are located near the paleowetland deposits, which suggests that local inhabitants exploited these water sources during late pre-Hispanic times. Results of this study improve knowledge of settlement patterns during this and earlier cultural periods.
Keywords: holocene; central andes; atacama desert; tuff; volcanic ash; desert wetlands; perched wetlands; late intermediate period